Prospering in the southern Africa's VUCA world of the nineteenth century: A case of resilience of Basotho of Lesotho. Issue 2 (9th May 2016) - Mofuoa, Khali
Abstract : Purpose: This paper aims to discuss the notion of resilience in the context of the Basotho of Lesotho who managed prospering as a nation in the era of uncertainty during the "VUCA" world of the nineteenth-century southern Africa. Design/methodology/approach: Using historical data from leadership and organizational behaviour perspectives, the theoretical context of the paper is established to inform discussion on the resilience of the Basotho during the "VUCA" world of the nineteenth-century southern Africa. Findings: The paper has established that the notion of resilience was synonymous to Basotho's way of life and livelihood during the "VUCA" world of the nineteenth-century southern Africa. The paper has also established that resilience became the key quality of Basotho as they continued prospering as a nation in the era of uncertainty during the "VUCA" world of the nineteenth-century southern Africa. Originality/value: From both leadership and organizational behaviour perspectives, the paper uses mainly historical data that are considered to be most relevant, valid and reliable to inform discussions on the notion of resilience as it relates to the Basotho as a nation during the "VUCA" world of the nineteenth-century southern Africa.